Th17 and CD24hiCD27+ regulatory B lymphocytes are biomarkers of response to biologics in rheumatoid arthritis. Issue 1 (December 2017) - Salomon, Sarah; Guignant, Caroline; Morel, Pierre; Flahaut, Gauthier; Brault, Clément; Gourguechon, Clément; Fardellone, Patrice; Marolleau, Jean-Pierre; Gubler, Brigitte; Goëb, Vincent
Abstract Background The aim was to describe the regulatory B and T cells (Breg and Treg) and T helper 17 (Th17) lymphocytes before and under treatment with biologic drugs, and to assess their potential predictive value as biomarkers of response in rheumatoid arthritis (RA). Methods This was a non-randomised, single-centre, prospective study. Patients with active RA (American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) 2010) who required the initiation or switch to any biologic drug except rituximab were included. The main judgement criterion was the frequency and absolute number of CD24hi CD27+ Breg and CD24hi CD38hi T2/Breg cells, CD25hi CD127low Treg and CD45RA− CD161+ CCR6+ Th17 cells measured at inclusion in both patients and controls, and after 1, 3 and 6 months of treatment (M1, M3 and M6) in patients with RA, and compared with the M6 response to treatment (EULAR response and Disease Activity Score in 28 joints (DAS28) remission). Results Thirty-one patients with RA and 17 controls were included. There was a reduction in T2/Breg frequency at M0 in patients (p < 0.001) and absolute numbers (p = 0.014) and in immunopositive vs. immunonegative RA (p = 0.016). DAS28 remission at M6 was associated with increased frequency of Treg (p = 0.01). A higher level of CD24hi CD27+ Breg at baseline was associated with DAS28 remission at M6 (p = 0.04) and a good EULAR response at M6 for abatacept-treated patients (p = 0.01). A lower M0 level of Th17 was associated with a good EULAR response at M6 (p = 0.007), notably under anti-cytokine drugs (p = 0.048). Conclusions Altogether, these data, although preliminary, suggest that phenotyping of T and B cells has potential value for the stratification of biologic drugs, notably with respect to choosing between abatacept and anti-cytokine blockade.